Respuesta :

Answer:

Here we know that:

[tex]m(v) = \frac{M_0}{\sqrt{1 - \frac{V}{C} } }[/tex]

Where V is the speed, C = 3*10^8 m/s

We want to solve:

[tex]m(v) = \frac{M_0}{\sqrt{1 - \frac{V}{C} } } = 2*M_0[/tex]

We can just isolate V from the above equation, so we will get:

[tex]\frac{M_0}{\sqrt{1 - \frac{V}{C} } } = 2*M_0[/tex]

[tex]\frac{1}{\sqrt{1 - \frac{V}{C} } } = 2[/tex]

[tex]1 = 2\sqrt{1 - \frac{V}{C} }[/tex]

[tex](1/2)^2 = 1 - \frac{V}{C}[/tex]

[tex]V = (1 - (1/4))*C = (3/4)*C = (3/4)*3*10^8 m/s = (9/4)*10^8 m/s[/tex]

That is the velocity such that the effective mass is twice the rest mass.

ACCESS MORE